Контуры социальной сингулярности:существование в распадающемся состоянии - Утюж, И. Г.; Утюж, Ірина Геннадіївна; Utyzh, I. H. (My University, 2017)
У статті аналізуються проблеми суспільства, людини, пов’язані з образами майбутнього. Розглядається сучасна ситуація соціального як «розпаду», «межі», «безперервного переривання» або як сингулярність. У статті феномен сингулярності концептуалізується як символічність індивіда в умовах соціального порядку або квазі-порядку. The problems of society and human that are associated with images of the future are analyzed in the article. The present situation of the social as "disintegration", "limit", "continuous interruption" or singularity is considered. The singularity phenomenon as the symbolism of an individual in conditions of order or quasi-order is conceptualized in the article. Modern society enters the model of an individualized space, where "private" prevails over "social". Personal and public remain inextricably linked, but human life is no longer an interaction with society but more a "biographical resolution of systemic contradictions", to the emergence of which for the most part it doesn’t belong. Individualization is a denial of social forms, individualization is for long, individualization is the concept of "individual - lone person – singularity", megastructures` epoch is over. And then what awaits us? After all, the paradox and tragedy for modern man is that his "narcissistic libido" (J. Lipovecki) still needs someone else. There is no point to discuss the political, economical component of this problem in this article. We as philosophers have to establish the fact that all the attempts to make social transformations on the platform of economism and politicalism are failing. Most of the decision-makers still do not realize that primarily people live in the mental and spiritual world, in the world of individual characteristics and passions, and only then in the state, economic, political space. Today as much as possible we don’t want to notice that not only in the post-Soviet space, but in the whole European world there is a crisis of the existing form of state (democratic) power and its institutions. Lyotard calls this situation an ideological disintegration: "distrust of methanarratives" and mercantilization of knowledge. J. Derrida presents modern reality as continuous deconstruction, the absence of real production and life in the simulation reality, as well as the social implosion – explosion which is turned inward (J. Baudrillard), and as a result, the appearance of the phenomenon of quasi-sociality (the continuous chaotic polylogic production of virtual images which are activating unpredictably, embodying in reality – rhizomes (J. Deleuze).
Контури соціальної сингулярності: існуванні в стані розпаду
Contours of social singularity: existence in the disintegrating state
Keywords: сингулярність; образи майбутнього; радикальна суб'єктивність; глобалізація; індивід; соціальність; singularity; images of the future; radical subjectivity; globalization; individual; sociality